2009
DOI: 10.1007/s11130-009-0114-3
|View full text |Cite
|
Sign up to set email alerts
|

Folates Stability in Two Types of Rye Breads During Processing and Frozen Storage

Abstract: High-performance liquid chromatography was used to study the stability of folate vitamers in two types of rye breads after baking and 16 weeks of frozen storage. Bread made using sourdough seeds contained less total folate (74.6 microg/100 g dry basis, expressed as folic acid) than the whole rye flour (79.8 microg/100 g dry basis) and bread leavened only with baker's yeast (82.8 microg/100 g dry basis). Most importantly, it was generated by a significant decrease in 5-CH3-H4folate form. The baking process caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…Two main mechanisms are described as being involved in folate losses, leaching into the surrounding liquid and oxidation during heat treatment [ 35 ]. The effect of different processing methods on folate content using the most common plant origin sources, such as legumes, grain products, green leafy and other vegetables, has been studied in recent years [ 32 , 36 , 37 , 38 , 39 , 40 ]. Delchier et al [ 41 ] reviewed folate content and stability in fruit and vegetables under most studied processes such as boiling, blanching, steaming, freezing, canning and juicing.…”
Section: Resultsmentioning
confidence: 99%
“…Two main mechanisms are described as being involved in folate losses, leaching into the surrounding liquid and oxidation during heat treatment [ 35 ]. The effect of different processing methods on folate content using the most common plant origin sources, such as legumes, grain products, green leafy and other vegetables, has been studied in recent years [ 32 , 36 , 37 , 38 , 39 , 40 ]. Delchier et al [ 41 ] reviewed folate content and stability in fruit and vegetables under most studied processes such as boiling, blanching, steaming, freezing, canning and juicing.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, more 5-CH 3 -H 4 folate than 5-HCO-H 4 folate has been found in rice (De Brouwer et al, 2010;Pfeiffer et al, 1997). Kariluoto et al (2004) reported that rye flour contained almost equal amounts of 5-CH 3 -H 4 folate and 5-HCO-H 4 -folate, and Gujska, Michalak, and Klepacka (2009) reported that 5-CHO-H 4 folate was the dominant vitamer in rye flour. In a few previous HPLC studies, 10-HCO-H 2 folate was determined in wholegrain rye flour (Gujska et al, 2009;Kariluoto et al, 2001Kariluoto et al, , 2004Shewry et al, 2010) and in wholegrain wheat flour Piironen et al, 2008).…”
Section: Folate Vitamer Distributionmentioning
confidence: 99%
“…Eluted samples were filtered (0.45-m nylon membrane filters) into HPLC vials and sealed with aluminum crimp caps (all items from Infochroma, Zug, Switzerland). HPLC analysis of the purified samples was performed in duplicate as described by Gujska et al [32] on a reversed-phase C18 column (Luna 250 mm × 4.6 mm; 5 m particle size; Phenomenex Inc., Torrance, CA, USA) with a reversed-phase C18 guard cartridge (ODS 4.0 mm × 3.0 mm; 5 m particle size; Phenomenex Inc.) with a LiChroGraph HPLC system (Merck Hitachi, Darmstadt, Germany) equipped with L-7100 pump, L-7200 autosampler with a Peltier sample cooler, a column oven II plus, L-7455 DAD Detector, and D-7000 HPLC system manager. Elution using acetonitrile in 0.033 M H2PO4 (pH 2.3) was done as follows: 0-8 min, 5% (v/v) acetonitrile; 8-25 min, linear gradient from 5 to 82% (v/v) acetonitrile; 25-30 min, 82% (v/v) acetonitrile; 30-32 min, linear gradient from 82 to 5% (v/v) acetonitrile; 32-40 min, 5% (v/v) acetonitrile.…”
Section: Folate Analysis With Hplcmentioning
confidence: 99%